Key Technologies in Physical Layer of 5G Wireless Communications Network - Shanjin Ni; Junhui Zhao (Dianxin kexue)
The continuously increasing demand of wireless communications impels the fast development of the next generation wireless communication technology. The 5G communication technology, which scheduled to be commercialized in the year beyond 2020, is still on its earlier stage. Based on the development history of wireless communications, the latest trend in the development of the wireless communications at home and abroad was presented. In order to solve the shortage of spectrum resources and improve the capacity of system, two key technologies of physical layer（millimeter-wave communications and massive MIMO）were introduced and remarked. Furthermore, the scenarios and development trend of 5G mobile communication systems in the future were also described.